2022
DOI: 10.1002/joe.22176
|View full text |Cite
|
Sign up to set email alerts
|

Understanding passengers’ satisfaction and loyalty towards ridesharing services

Abstract: This study examines the ridesharing services in a developing economy, with the aim of revealing the factors influencing passengers’ satisfaction and loyalty. This study is important as the ridesharing industry is growing at a tremendous rate and will ultimately attract many new players in the market. Offered abundant choices, consumers are exploring the best ridesharing services that meet their satisfaction. As the switching costs and brand loyalty are lower for on‐demand services, it is pertinent to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 131 publications
(124 reference statements)
1
12
0
Order By: Relevance
“…Taken collectively, it is hoped that this article will serve as a useful resource to help authors choose good research topics for GBOE and premier journals at large. It is also hoped that readers will be delighted with the selection of articles in GBOE ’s latest issue focusing on de‐internationalization (Lim & Mandrinos, 2023), knowledge hiding (Koay & Lim, 2023), and ridesharing (Shamsudin et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken collectively, it is hoped that this article will serve as a useful resource to help authors choose good research topics for GBOE and premier journals at large. It is also hoped that readers will be delighted with the selection of articles in GBOE ’s latest issue focusing on de‐internationalization (Lim & Mandrinos, 2023), knowledge hiding (Koay & Lim, 2023), and ridesharing (Shamsudin et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, Shamsudin et al. (2023) did a survey of 200 ridesharing passengers to provide insights into ridesharing passengers’ post‐purchase evaluations. Noteworthily, the study revealed that both brand image and price significantly influence customer satisfaction.…”
Section: Hot Of the Pressmentioning
confidence: 99%
“…Grounded in the expectancy–disconfirmation theory, satisfaction emerges from the alignment between consumers' initial expectations and perceived performance (Hsu & Lin, 2023). Consequently, individuals experiencing heightened satisfaction tend to manifest pronounced loyalty, evident through favorable behaviors such as repeat purchases, recommendations, and resistance against competitive enticements (Shamsudin et al, 2023). This theory's foundational premise underscores the importance of adeptly managing consumer expectations and consistently delivering exceptional products or services (Hsu & Lin, 2023; Shamsudin et al, 2023).…”
Section: Literature Review and Research Hypotheses Developmentmentioning
confidence: 99%
“…This includes a wide range of factors, such as the friendliness and helpfulness of the staff, the cleanliness and condition of the rooms and common areas, the availability of amenities and activities, the efficiency of check-in and check-out processes, and the overall atmosphere of the resort. To maintain high levels of service quality (Lim et al, 2022, Shamsudin et al, 2023), resorts must constantly strive to meet and exceed the expectations of their guests. Further, some additional aspects of service quality that are important in resorts are, namely, attention to detail—this refers to the resort’s ability to anticipate and address the needs of its guests.…”
Section: Introductionmentioning
confidence: 99%